Comparison of Glasgow Outcome Scale (GOS) and Glasgow Coma Scale (GCS) between Surgical and Conservative Management of Spontaneous Supratentorial Intracerebral Hemorrhage Patients: A Randomized Control Trial - Islam, Mohammad Rafiqul; Khan, Md Shafiqul Kabir; Rahman, Md Mahfuzur; Talukder, Moajjam Hossain; Karim, Md Rezaul; Salam, Abdus (Journal of Current and Advance Medical Research, 2018)
Background: Glasgow outcome scale (GOS) and Glasgow Coma Scale (GCS) were the important parameter for the proper management of spontaneous supratentorialintracerebral hemorrhage patients. Objective: The purpose of the present study was to compare the GOS and GCS between surgical and conservative management of spontaneous supratentorialintracerebral hemorrhage patients. Methodology: This randomized control trial was conducted in the Department of Neurosurgery at Dhaka Medical College and Hospital from January 2010 to October 2011 for a period of one year and ten months. All hypertensive patients with spontaneous supratentorial intracerebral hemorrhage who were admitted within 48 hours of stroke in Neurosurgery Department during the study period were considered as a study population. Patients underwent surgery was considered as group I and patients those who did not give the consent for operation were treated conservatively was considered as group II. Result: A total of 31 patients were enrolled in this study of which 14 patients underwent surgical evacuation and 17 patients were selected for conservative therapy. Significant positive correlation was found between the GCS score on admission and GOS at 30 days follow-up in surgery group (r=0.649; p<0.05). But a positive significant correlation (r=0.613; P=0.020) was between GCS follow up with GCS on admission in surgery patients and (r=0.575; P=0.016) in conservative group. Conclusion: In conclusion both GOS and GCS are essential during the management of surgical and conservative spontaneous supratentorialintracerebral hemorrhage patients. Journal of Current and Advance Medical Research 2018;5(2):49-54